Lipid-lowering statins and polyphenol-based supplementation: a scoping review on drug-food interaction potential - Costa, Rita; Ferreira, Carolina; Alves, André; Nunes, Sara; Reis, Flávio; Malva, João; Viana, Sofia (Frontiers in Pharmacology, 2025)
BackgroundLifestyle modifications, particularly the adoption of healthy dietary patterns such as the Mediterranean Diet (MedDiet), are foundational in any treatment plan, including for patients prescribed first-line statin therapy for hypercholesterolemia. However, the rising popularity of MedDiet-associated foods and nutraceuticals among health-conscious consumers has raised concerns about their potential interactions with statins, potentially leading to adverse effects. One notable example involves polyphenol supplements, a class of anti-dyslipidemic phytochemicals known to influence statins’ pharmacokinetics. Still, whether chronic polyphenol exposure achieves plasma concentrations sufficient to alter statin pharmacokinetics in clinical settings is controverse. Moreover, it remains unclear which key biological targets are shared by both classes of molecules and how they mediate potential pharmacokinetic and pharmacodynamic interactions. This study aims to systematically map reported statin-polyphenol interactions and identify the principal biological targets involved, elucidating their impact on statin pharmacokinetics, efficacy, and toxicity.MethodsA scoping review was conducted using the PubMed/Medline, Scopus, and Web of Science databases. This work was designed in accordance with PRISMA-ScR. The review protocol was registered in the Open Science Framework.ResultsStatin-polyphenol interactions were reported in 83.9% of the studies analyzed. The biological targets mediating these interactions play chief roles in statins’ cellular uptake (OATP/P-glycoprotein), metabolism (CYP450/intestinal esterases), and core mechanisms underlying statin action, namely, HMG-CoA reductase inhibition. Polyphenols significantly influenced statin pharmacokinetics, altering total drug exposure (AUC) and extent (Cmax), either by enhancement or inhibition, with apparently less impact on statins’ absorption rate (Tmax). At the clinical level, only five studies addressed statin-polyphenol interactions, yielding conflicting results on the potential enhancement of therapeutic efficacy and adverse effects.DiscussionThis work presents an integrated perspective on the cellular and molecular mechanisms underlying statin–polyphenol interactions. It highlights substantial inter-individual variability linked to conflicting evidence, from synergistic effects enabling lower statin doses and reduced adverse events to potential exacerbation of side effects. These findings underscore the need for controlled studies to clarify the clinical relevance of polyphenol-induced alterations in statin pharmacokinetics and pharmacodynamics. Such data are essential to develop evidence-based guidelines that may optimize statin therapy and support individualized treatment strategies.Systematic review registrationidentifier 10.17605/OSF.IO/DJW5G.